(untitled) (Bioagro, 2023)
The development of mini lettuce genotypes with good agronomic characteristics are fundamental to launch new cultivars. Thus, the objective was to compare the variability of biofortified mini lettuce genotypes by analyzing its principal components and hierarchical clusters and evaluate different selection indices to estimate selection gain. The experiment was carried out at the Federal University of Uberlândia in a randomized block design implemented with 11 treatments (10 genotypes of mini lettuce generation F5:6 and one mini lettuce commercial cultivar) and four repetitions. The following variables were evaluated: chlorophyll content (SPAD índex), stem diameter and length, plant diameter and height, number of leaves per plant, fresh mass of the aerial part, and bolting tolerance. The data were submitted to analysis of variance and genotypes were compared using the Scott-Knott test (P≤0.05). Additionally, principal components, hierarchical clusters, and correlation were evaluated (P≤0.05). The best genotypes were chosen by appropriate direct and indirect selection and the main indices: William’s index, selection index from Smith and Hazel, and Mulamba y Mock index. There were five groups and a significant negative correlation of all agronomic characteristics evaluated with resistance to bolting, except stem length. William’s index provided a balanced distribution of genetic gains by selecting the genotypes UFU 66#8, UFU 215#2, UFU 215#7 and UFU 215#13.